Eficiência produtiva e deposição de produtos fitossanitários em cultivares de soja submetidas à a aplicação de lactofen - Rosa, Willian Pelisser da (2017)
Several factors limit the productivity of soybeans, leading to a decrease in yield ceiling. Excessive plant growth is one of these factors. The objective of this study was to evaluate if the use of lactofen increases the productive efficiency of soybean. Two experiments were carrie d out with cultivars NA 5909 RG and BMX Power RR. The experimental design was used in a randomized complete block, with four treatments and five replicates: T1: control, T2: application of 140 g ai/ha of lactofen in the V3 phenological stage, T3: application of 140 g ai/ha of lactofen at the phenological stage V6 and T4: application of 70 g ai/ha of lactofen in the phenological stage V3 + 70 g ai/ha of lactofen in the phenological stage V6.The following variables were evaluated: number of nodules and dry mass of nodules per plant (g); volume (cm³/m²), specific surface area (cm²/m²), dry mass (g/m²) and length (cm) of roots; height (cm) number of leaflets, total number of nodes, productive and unproductive in the stem, number of ramitications, diameter of the stem (mm), internodes length (mm), between nodes 4º/5º, 5º/6º, 6º/7º and 7º/8º per plant; leaf area index (LAI) and leaf area of each leaflet (cm²); Interception of photosynthetically active solar radiation (µmol m²/s) in the upper and lower strata of the canopy of the culture and extinction coefficient of the culture (k); percentage of area covered and impact of drops per cm², in the different thirds, via spraying; number of vegetables and total of vegetables per third, number of grain failures in vegetables and total grain failure in vegetables per third, number of grains and mass of grains (g) per thirds, mass of one thousand grains and grain hectare. The plant architecture was influenced by the treatments, and in the phenological stage R1 the plants that received lactofen application presented smaller stature compared to the control. For the cultivar NA 5909 RG, there was a decrease in the LAI. The interception of solar radiation in the lower stratum of plants showed an increase in all treatments that received lactofen application. The use of lactofen provided an expressive increase in the coverage percentage and in the number of drops per cm² by spraying in the middle and lower thirds of the plants. The main influence of lactofenwas observed in the lowerthird of the plants where it provided an increase in the number of productive nodes, number of vegetables and number of grains. The use of lactofen provided an increase in productivity for the